Conjugate Gradient Method for System of Linear Algebraic Equations (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Conjugate Gradient Method is an iterative technique for solving large sparse systemsof linear equations. As a linear algebra and matrix manipulation technique, it is a usefultool in approximating solutions to linearized partial differential equations. Thefundamental concepts are introduced and utilized as the foundation for the derivation ofthe Conjugate Gradient Method